Sustainable Textile Marketing - Memon, Hafeezullah; Jin, Xiaoke; Tian, Wei; Zhu, Chengyan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
We know that sustainability has become an important topic in every aspect of life. The textile, fashion, and material industries must also be sustainable, which could be imparted in their development, production, or even marketing. The textile industry has a huge market, as clothing is arguably the most important human need after food. Recently, this industry has been labeled as a polluting industry, a label that could be overcome by the proper development of textile goods and careful marketing strategies. There are specific roles that government, entrepreneurs, and even universities can play in properly educating people to make the textile industry cleaner and greener. Several journals focus only on one of the aspects of this key problem, i.e., the production of sustainable materials, textile education, or textile marketing. However, herein, we strive to bring different areas together on one platform to cover different aspects, i.e., production, policy, education, and marketing related to textile fashion and textile materials.